Effects of COVID‐19‐Related Racial Discrimination on Depression and Life Satisfaction Among Young, Middle, and Older Chinese Americans. Issue 2 (10th October 2021) - Litam, Stacey Diane Arañez; Oh, Seungbin
Abstract : This study examined the relationship between age and gender on Chinese American adults' (N = 184) experiences of COVID‐19‐related racial discrimination, depression, and life satisfaction. Results indicated that COVID‐19‐related racial discrimination explained 47.9% of the variance in depression, and COVID‐19‐related racial discrimination and depression explained 42.3% of the variance in life satisfaction.